The development of multiplex STR panels for the identification of bald eagles (Haliaeetus leucocephalus) and golden eagles (Aquila chrysaetos) - Darren J. Wostenberg; Mary K. Burnham-Curtis (Forensic Science International: Animals and Environments, 2023)
The ability to reliably genotype individual bald eagle (Haliaeetus leucocephalus) and golden eagle (Aquila chrysaetos) samples has proven to be a valuable forensic tool for investigations of illegal trafficking of eagle feathers and body parts. Twenty STR loci were assembled into three optimized multiplex STR panels. The three STR multiplex PCRs include loci ranging from dinucleotide to pentanucleotide motifs, and both monomorphic and polymorphic amplification. The number of alleles for bald eagles ranged 1–5 (14 polymorphic loci), and the number of alleles for golden eagles ranged from 1 to 11 (16 polymorphic loci). Bald and golden eagles shared alleles at 5 loci, the other 15 loci yielding alleles characteristic of each species. These multiplex panels will be useful in wildlife law enforcement investigations in which eagle feathers and body parts can be identified to species and individuals matched to link a crime scene and eagle victim to a suspect.